Recent developments in the use of electrokinetic methods for rapid cell viability assessments and separations - Blanca H. Lapizco-Encinas (Journal of Chromatography Open)
Rapid cell viability assessments are essential in a growing number of fields, including clinical analysis, healthcare, drug development and food safety. Electrokinetic (EK) methodologies have proved to be robust and reliable platforms of the analysis of cells, including viability assessments. Discussed here are applications of two EK phenomena, dielectrophoresis and electrophoresis, which can discriminate cells by their viability status and also sort and separate cells into separate viable and nonviable fractions, so further analysis can be performed. For each EK method, the operating principle is presented, followed by a brief historical overview and a detailed analysis of recent reports published between 2015 and 2024. The concluding remarks include a summary of the content of this review article and present a future perspective on the expected future advances on EK-based systems for the assessment and separation of cells based on their viability status.